The Architecture of Fiqh Muamalat Based on The Geometry of Equilibrium in the Islamic Tourism Ecosystem - Riyanto Sofyan; Ida Busnetty; Aa Hubur; Soeharjoto Soeharjoto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The massive growth of the global Muslim travel market demands a rigorous business governance model. While Indonesia has integrated Muslim-friendly tourism into RPJMN 2025–2029 via Perpres No. 12/2025, a legal vacuum persists following the revocation of Permenparekraf No. 2/2014, leading to policy fragmentation and "halal-washing" risks. This study aims to address this dichotomy by proposing a comprehensive blueprint based on the "Geometry of Equilibrium" in Islamic economics. Employing a qualitative-descriptive framework with a legal-normative approach, this research evaluates the integration of sharia contracts into state regulations. The findings reveal that the Geometry of Equilibrium harmonizes profitability, ecology, and social welfare by synthesizing Ibadah, Khilafah, and Maslahah. Furthermore, the "Red Zone" matrix stabilizes the market by prohibiting israf, tabzir, riba, and ihtikar, while a precise "Contract Taxonomy" structures the supply chain. This study concludes that transforming Fatwa DSN-MUI No. 108/2016 from soft law into binding hard law set at a Ministerial Regulation level is an absolute prerequisite to eliminate policy fragmentation, realize national strategic targets, and enhance global competitiveness.